Transcranial Direct Current Stimulation Combined With Listening to Preferred Music Alters Cortical Speech Processing in Older Adults - Bidelman, Gavin M.; Chow, Ricky; Noly-Gandon, Alix; Ryan, Jennifer D.; Bell, Karen L.; Rizzi, Rose; Alain, Claude (Frontiers in Neuroscience, 2022)
Emerging evidence suggests transcranial direct current stimulation (tDCS) can improve cognitive performance in older adults. Similarly, music listening may improve arousal and stimulate subsequent performance on memory-related tasks. We examined the synergistic effects of tDCS paired with music listening on auditory neurobehavioral measures to investigate causal evidence of short-term plasticity in speech processing among older adults. In a randomized sham-controlled crossover study, we measured how combined anodal tDCS over dorsolateral prefrontal cortex (DLPFC) paired with listening to autobiographically-salient music alters neural speech processing in older adults compared to either music listening (sham stimulation) or tDCS alone. EEG assays included both frequency-following responses (FFRs) and auditory event-related potentials (ERPs) to trace neuromodulation-related changes at brainstem and cortical levels. Relative to music without tDCS (sham), we found tDCS alone (without music) modulates the early cortical neural encoding of speech in the time frame of ~100-150 ms. Whereas tDCS by itself appeared to largely produce suppressive effects (i.e., reducing ERP amplitude), concurrent music with tDCS restored responses to those of the music+sham levels. However, the interpretation of this effect is somewhat ambiguous as this neural modulation could be attributable to a true effect of tDCS or presence/absence music. Still, the combined benefit of tDCS+music (above tDCS alone) was correlated with listeners’ education level suggesting the benefit of neurostimulation paired with music might depend on listener demographics. tDCS changes in speech-FFRs were not observed with DLPFC stimulation. Improvements in working memory pre to post session were also associated with better speech-in-noise listening skills. Our findings provide new causal evidence that combined tDCS+music relative to tDCS-alone (i) modulates the early (100-150 ms) cortical encoding of speech and (ii) improves working memory, a cognitive skill which may indirectly bolster noise-degraded speech perception in older listeners.